Suppression of Myc, but not E1a, transformation activity by Max-associated proteins, Mad and Mxi1. - Lahoz, E G (1994)
Mad and Mxi1, two members of the Myc-related basic-region helix-loop-helix/leucine-zipper family of proteins, associate directly with Max to form sequence-specific DNA binding heterodimers that are transactivation-incompetent. Mad-Max complexes have been shown to exert a strong repressive effect on Myc-induced transactivation, perhaps through the competitive occupation of common promoter binding sites also recognized by active Myc-Max heterodimers. To place these recent biochemical observations in a biological context, mad and mxi1 expression vectors were tested for their ability to influence Myc transformation activity in the rat embryo fibroblast cooperation assay. Addition of an equimolar amount of mad or mxi1 expression vector to mouse c-myc/ras cotransfections resulted in a dramatic reduction in both the number of foci generated and the severity of the malignant phenotype. Myc-specific suppression by Mad and Mxi1 was demonstrated by their ability to affect c- and N-myc-, but not ela-, induced transformation. In contrast, mad and mxi1 expression constructs bearing deletions in the basic region exerted only mild repressive effects on Myc transformation activity, suggesting that occupation of common DNA binding sites by transactivation-incompetent Mad-Max or Mxi1-Max complexes appears to play a more dominant role in this suppression than titration of limited intracellular pools of Max away from active Myc-Max complexes. Thus, these biological data support a current model for regulation of Myc function in which relative intracellular levels of Mad and Mxi1 in comparison to those of Myc may determine the degree of activation of Myc-responsive growth pathways.